AI-Assisted Bibliometric Mapping of Global Research on Technology-Based Training for Enhancing School Principals' Managerial Competence in the Digital Transformation Era - Sabariah, Sabariah; Rufi'i, Rufi'i; Bandono, Adi; Hakim, Luqmanul; Suharti, Suharti; Chandra, Dani; Novta, Novta; Netty, Netty (Universitas Dharma Wacana, 2025)
Digital transformation demands that school principals possess technology-based managerial competencies to lead innovation, improve organizational effectiveness, and create inclusive learning environments in the dynamic era of global education. This article describes trends, thematic focuses, and global collaborations in technology-based educational leadership research to strengthen principals' managerial competencies in facing the challenges of digital transformation and inclusive education. The research methodology uses an artificial intelligence (AI)-assisted bibliometric approach with quantitative-descriptive analysis, including Scopus data extraction, cleaning, normalization, visualization, and validation of results through NLP and clustering topic modeling. The analysis shows significant publication growth since 2010 with a peak in the 2024–2025 period, driven by the accelerated adoption of educational technology after the COVID-19 pandemic. The rate of publication increase reached 6.63% per year, with an average of 11.74 citations per document. Dominant themes include educational leadership, school principals, instructional leadership, and professional development, while new topics such as digital leadership, gender equality, and policy innovation began to strengthen post-2020. Affiliation mapping shows the dominance of universities from Spain, South Africa, and Israel, followed by an increase in contributions from Asian institutions (Indonesia and Malaysia) since 2016. The most productive author is ARAR KH (8 publications), followed by DOR-HAIM P. and HALLINGER P., who are the main nodes of the global network. Cross-country collaboration has been shown to increase the number of citations and strengthen the research network. The study highlights the shift in principal leadership from traditional models to data-driven digital ones, emphasizing technology integration, global collaboration, ethics, and managerial competencies in facing the challenges of digital-era education.